2022
DOI: 10.3390/ijerph192013613
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Fire at an Illegal Landfill in Southern Poland on the Formation of Toxic Compounds and Their Impact on the Natural Environment

Abstract: Landfill fires pose a real threat to the environment as they cause the migration of pollutants to the atmosphere and water sources. A greater risk is observed in the case of wild landfills, which do not have adequate isolation from the ground. The aim of this article is to present the results of studies on the toxicity of waste from a fire in a landfill in Trzebinia (southern Poland). Both soil and waste samples were investigated. The samples were analyzed using the GC-MS method and the leachates using ICP-OES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
2
9
0
Order By: Relevance
“…Filipponi et al (2003) also identified Zn as one of the main trace elements in incineration ashes from municipal waste incinerators, a finding confirmed by the present study [36]. Similarly, Rykała et al (2022), while analyzing ashes from an illegal waste storage sites fire, observed that Zn constituted the largest share of metals, although at significantly higher levels compared to this study, averaging 18.47 mg/kg [21].…”
Section: Content Of Selected Compounds In Samples Of Ash From Wildfir...supporting
confidence: 89%
See 3 more Smart Citations
“…Filipponi et al (2003) also identified Zn as one of the main trace elements in incineration ashes from municipal waste incinerators, a finding confirmed by the present study [36]. Similarly, Rykała et al (2022), while analyzing ashes from an illegal waste storage sites fire, observed that Zn constituted the largest share of metals, although at significantly higher levels compared to this study, averaging 18.47 mg/kg [21].…”
Section: Content Of Selected Compounds In Samples Of Ash From Wildfir...supporting
confidence: 89%
“…According to Tomaškinová et al (2014), the chloride content in waste at the largest illegal landfill in the Ko ńska Diera chasm in Slovakia was below 40 mg/kg [38]. Rykała et al (2022) reported an average chloride content of 51.9 mg/kg, with maximum values reaching 320 mg/kg [21]. In the present study, only at site 2 were these values below 40 mg/kg (25 mg/kg), while at the other sites, they were significantly higher and ranged from 187 mg/kg (site 5) to 4907 mg/kg (site 1), which may result in a higher level of risk to the environment and people.…”
Section: Content Of Selected Compounds In Samples Of Ash From Wildfir...mentioning
confidence: 99%
See 2 more Smart Citations
“…For PM10, the instruments showed the highest concentration at an average level of 14 µg/m 3 , and for CO, the concentration was recorded at an average level of 22.8 ppm 27 . Reference levels of pollutants in the air for the protection of human health were taken into consideration based on the impact of CO, RI, HCHO, NH 3 , H 2 S, SO 2 , NO 2 , and Cl 2 for a 30-min inhalation and the average value measured over 24 h for PM10 28 – 30 . These were compared with the highest recorded values during the measurement for the components mentioned (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%